Nanotechnology-Aided Advancement in Combating the Cancer Metastasis - Arun Kumar Singh; Rishabha Malviya; Bhupendra Prajapati; Sudarshan Singh; Deepika Yadav; Arvind Kumar (MDPI AG, 2023)
Modern medicine has been working to find a cure for cancer for almost a century, but thus far, they have not been very successful. Although cancer treatment has come a long way, more work has to be carried out to boost specificity and reduce systemic toxicity. The diagnostic industry is on the cusp of a technological revolution, and early diagnosis is essential for improving prognostic outlook and patient quality of life. In recent years, nanotechnology's use has expanded, demonstrating its efficacy in enhancing fields such as cancer treatment, radiation therapy, diagnostics, and imaging. Applications for nanomaterials are diverse, ranging from enhanced radiation adjuvants to more sensitive early detection instruments. Cancer, particularly when it has spread beyond the original site of cancer, is notoriously tough to combat. Many people die from metastatic cancer, which is why it remains a huge issue. Cancer cells go through a sequence of events known as the "metastatic cascade" throughout metastasis, which may be used to build anti-metastatic therapeutic techniques. Conventional treatments and diagnostics for metastasis have their drawbacks and hurdles that must be overcome. In this contribution, we explore in-depth the potential benefits that nanotechnology-aided methods might offer to the detection and treatment of metastatic illness, either alone or in conjunction with currently available conventional procedures. Anti-metastatic drugs, which can prevent or slow the spread of cancer throughout the body, can be more precisely targeted and developed with the help of nanotechnology. Furthermore, we talk about how nanotechnology is being applied to the treatment of patients with cancer metastases.